Hubungan antara Trait Personaliti dengan Tingkah Laku Kepimpinan (Sains Humanika, 2014)
The main objective of this cross-sectional study is to determine the inter relationship of personality trait (Conscientiousness, Openness to experience, Extraversion, Agreeableness) and transformational leadership among school educator leaders in High Performance Schools (SBT). Two sets of questionnaire to measure leadership behavior and personality trait were administered to 306 (89%) (132 = male; 174 = female) and subjects who were selected by stratified random sampling in 15 SBT schools in Malaysia. Data were analyzed through inferential statistics such as correlation. The finding of the bivariate analysis using the Pearson correlation method indicates that the personality trait such as Conscientiousness (r=. 448, p
Keywords: Personality traits; transformational leadership; school leaders